Approximate Kelvin-Voigt Fluid Driven by an External Force Depending on Velocity with Distributed Delay. (11th October 2015) - Guo, Yantao; Cheng, Shuilin; Tang, Yanbin
Abstract : We consider the approximate 3D Kelvin-Voigt fluid driven by an external force depending on velocity with distributed delay. We investigate the long time behavior of solutions to Navier-Stokes-Voigt equation with a distributed delay external force depending on the velocity of fluid on a bounded domain. By a prior estimate and a contractive function, we give a sufficient condition for the existence of pullback attractor of NSV equation.